Shift to Impress: How Thai LGBTs Create New Terms in Their Daily Chats - Kanchanabundhu, Korapon; Trakulkasemsuk, Wannapa (rEFLections, 2022)
This research study aims to investigate word-formation strategies employed by Thai LGBTs in creating new terms. A number of LGBT terms were preselected from a Thai LGBT series named Diary Tootsies The Series, then validated by three external raters. The 50 remaining terms were analysed through an adapted framework of word formation (Algeo and Algeo, 1993; Bauer, 2020). The result indicates that Shift of Meaning, which is the strategy of assigning new meaning to the existing terms, was the predominant strategy employed. Shift of Meaning may possibly co-occur with some other strategies, such as using rhyme-motivated or compounding words. The use of more than one strategy may help embellish the terms and make their meaning more expressive and entertaining. As language can reflect its users’ identity, new terms created by Thai LGBTs would embrace the stereotypical image that people have about them in the ways that they are outgoing, funny, and creative.